Pandemic politics: The deadly toll of partisanship in the age of covid - Gadarian, Shana Kushner; Goodman, Sara Wallace; Pepinsky, Thomas B. (Princeton Princeton University Press, 2022)
COVID-19 has killed more people than any war or public health crisis in American history, but the scale and grim human toll of the pandemic were not inevitable. Pandemic Politics examines how Donald Trump politicized COVID-19, shedding new light on how his administration tied the pandemic to the president$1 (Bs political fate in an election year and chose partisanship over public health, with disastrous consequences for all of us.s
Keywords: Covid-19 Pandemic; Political aspects- United States; Medical Policy- United States